2016
DOI: 10.1039/c6py00281a
|View full text |Cite
|
Sign up to set email alerts
|

A polycationic covalent organic framework: a robust adsorbent for anionic dye pollutants

Abstract: A 2D polycationic covalent organic framework has been constructed, which exhibits a robust capability of adsorbing dye pollutants from water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
114
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(116 citation statements)
references
References 63 publications
(6 reference statements)
1
114
0
1
Order By: Relevance
“…Comprehensively, the strong adsorption capacity of pyrimidine‐linked ionic CMP, CMP‐PM‐Me , may be attributed to the formation of favorable soft base‐soft acid and hard base‐hard acid (Na + ) ion pairs which are caused by the exchange of dye anions as soft bases with I − anions as hard bases …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Comprehensively, the strong adsorption capacity of pyrimidine‐linked ionic CMP, CMP‐PM‐Me , may be attributed to the formation of favorable soft base‐soft acid and hard base‐hard acid (Na + ) ion pairs which are caused by the exchange of dye anions as soft bases with I − anions as hard bases …”
Section: Resultsmentioning
confidence: 99%
“…Comprehensively,t he strong adsorption capacity of pyrimidine-linked ionic CMP, CMP-PM-Me,m ay be attributedt ot he formation of favorable soft base-soft acid and hard base-hard acid (Na + )i on pairs which are caused by the exchange of dye anionsa ss oft bases with I À anionsa sh ard bases. [38] To make further studies of the adsorptionm echanism for CR, the adsorption isotherms and relevant parameters can be obtained by fitting againstt he Langmuir [Eq. (2)] and Freundlich [Eq.…”
Section: Dye Adsorption Performancementioning
confidence: 99%
“…[3] Covalent organic frameworks (COFs), [6][7][8][9][10] crystallinep orousm aterials formed by the self-assembly of purely organic building blocks, have been explored for aw ide range of applications, such as optoelectronics, [11][12][13] gas storage, [14] and catalysis. [15][16][17][18][19][20][21][22] COFs have also shown promise as adsorbents for organic dyes, [23][24][25][26][27] mercury, [28,29] radionuclides, [30] and lanthanides, [31] as carriers for drug delivery, [32][33][34] and isolation of industriallyr elevant compounds. [35] Recently, we demonstrated that COFs can be used to efficientlyc apture marine toxin okadaic acid from seawater.…”
mentioning
confidence: 99%
“…Although various POPs for adsorbing MB have been reported, the POPs with their maximum MB adsorption value over 2500 mg g −1 are rare 32–38. Specially, it is still challenging to develop practical POPs to remove MB from other pollutant with high selectivity, reusability, and efficient adsorption in aqueous solution 39–45…”
Section: Introductionmentioning
confidence: 99%